Izzivi slavistike v 21. stoletju: 4. mednarodna znanstvena konferenca Slavistični znanstveni premisleki, zbornik povzetkov - Marina Bajić; Nikolovski, Gjok (2021)
Challenges of Slavic Studies in the 21st Century: 4th International Scientific Conference Slavic Scientific Reflections, Book of Abstracts. The linguistic contributions include comparative-historical and dialectological research of Slavic languages, comparative research of modern Slavic languages, sociolinguistic, linguocultural and computer research of Slavic languages, research on the standardization and norms of Slavic languages. In the field of Slavic literature and cultures, we will address topics on Slavic literature in a comparative, interliterary and intercultural perspective, Slavic literature in film, theoretical aspects of the study of contemporary Slavic literature, the interrelationships of Slavic literature and cultures, translations of Slavic literature. The conference will also shed some light on the didactic aspect and perspectives of Slavic studies through the prism of the development of contemporary Slavic studies and the teaching of Slavic languages, literature and cultures.
Keywords: methodological approaches; research of Slavic languages; norm studies in Slavic languages; Slavic dialectologies; interdisciplinary research of Slavic languages; translations of Slavic literature; Slavic literature in the 21st century; Slavic literature in an intercultural context; film adaptations of Slavic literature; interdisciplinary research of Slavic literature; perspectives of slavic studies and the study programmes in slavic studies; transfer of knowledge into the educational process